Arbitrary mixture of two charged interacting particles in a magnetic Aharonov-Bohm ring: Persistent currents and Berry's phases - Kyriakou, Kyriaki; Moulopoulos, K.; Ghazaryan, A. V.; Djotyan, A. P. (My University, 2010)
Aharonov-Bohm physics at the two-particle level is investigated for distinguishable interacting charged particles through the exact solution of a toy model with confined states. The effect of the inaccessible magnetic flux is distributed between the center-of-mass and the internal pair level, and the nontrivial manner in which the two levels mutually affect each other demonstrates the interplay between interactions, the nontrivial topology, the Aharonov-Bohm flux and the characteristics of a charged quantal mixture. Analytical expressions for energy spectra, wavefunctions, (flux-dependent) critical interactions for binding and current densities are derived, and these offer the rare possibility of studying persistent currents from the point of view of an interacting nanoscopic system. Two cyclic adiabatic processes are identified, one coupled to the center-of-mass behavior and the other defined on the two-body interaction potential, with the associated Berry's phases also analytically determined; these are found to be directly linked to the electric and probability (persistent) currents in nontrivial ways that are shown to be universal (independent of the actual form of the interaction). The direct connection of the two-body Berry's phase to the electric current for a neutral system is found to disappear in the case of identical particles-hence revealing the character of a charged mixture as being crucial for exhibiting this universal behavior. © 2010 IOP Publishing Ltd.
Keywords: Gallium arsenide; Nanorings; Droplet epitaxy